NCAA Academic Performance Program (APP): Future Directions - Harrison, Walter (Journal of Intercollegiate Sport, 2012)
This paper represents the first major effort to conduct a comprehensive review of the National Collegiate Athletic Association (NCAA) Academic Performance Program (APP) and to recommend to the NCAA Board of Directors those modifications that will lead to further improvement in graduation performance. They fall into four categories: (a) new initial eligibility standards; (b) new requirements for 2-year college transfers; (c) new requirements for eligibility for postseason competition; and (d) new penalty structure and penalty thresholds. Conclusions and recommendations are offered.